Hubungan pemberian asi eksklusif terhadap kejadian diare Pada bayi usia 0-24 bulan - Dayana Noprida; Silma Rostika; Desi Kurniawati; Wahyu Dwi Fatimah (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Diarrhea is the leading cause of infant mortality and morbidity in developing countries. Diarrhea can be triggered by various factors, one of which is not exclusive breastfeeding. Infants who are exclusively breastfed until 6 months of age have fewer gastrointestinal disorders and growth disorders. Purpose: To determine the relationship between exclusive breastfeeding and the incidence of diarrhea in infants aged 0-24 months. Method: Quantitative research with cross-sectional research design. The population in this study were all children aged 0-24 months in the Gisting Health Center Working Area, with a sample of 66 respondents using the total sampling technique. Data collection using questionnaire. Univariate and bivariate analysis (chi square test). Results: It was found that 35 (53.0%) respondents practiced exclusive breastfeeding. and 52 (78.8%) respondents did not experience diarrhea. Conclusion: There is a relationship between exclusive breastfeeding and the incidence of diarrhea in infants aged 0-24 months at the Gisting Health Center in 2024 (p-value = 0. 003). Suggestion: Health workers can increase health promotion, especially regarding exclusive breastfeeding as an effort to prevent diarrhea in infants and provide education to mothers and families regarding additional food for babies.   Keywords: Diarrhea incidence; Exclusive breastfeeding; Infants aged 0-24 months.   Pendahuluan: Diare merupakan penyebab utama terjadinya mortalitas dan morbiditas pada bayi di negara berkembang. Diare dapat dipicu oleh berbagai faktor salah satunya ialah tidak dilakukannya pemberian ASI eksklusif. Bayi yang diberikan ASI eksklusif sampai usia 6 bulan lebih sedikit mengalami gangguan gastrointestinal dan gangguan pertumbuhan. Tujuan: Untuk mengetahui hubungan pemberian ASI eksklusif terhadap kejadian diare pada bayi usia 0-24 bulan. Metode: Penelitian kuantitatif dengan rancangan penelitian cross-sectional. Populasi dalam penelitian ini adalah semua anak usia 0-24 bulan Wilayah Kerja Puskesmas Gisting, dengan sampel yang digunakan sebanyak 66 responden menggunakan teknik total sampling. Pengumpulan data menggunakan lembar keusioner. Analisis secara univariat dan bivariat (uji chi squre). Hasil: Diketahui sebanyak 35 (53.0%) responden melakukan pemberian ASI eksklusif. dan sebanyak 52 (78.8%) responden tidak mengalami kejadian diare. Simpulan: Ada hubungan pemberian ASI eksklusif terhadap kejadian diare pada bayi usia 0-24 bulan di Puskesmas Gisting tahun 2024 (p-value =0. 003). Saran: Bagi tenaga kesehatan dapat meningkatkan promosi kesehatan terutama mengenai pemberian ASI eksklusif sebagai upaya preventif diare pada bayi dan pemberian edukasi pada ibu dan keluarga mengenai makanan tambahan untuk bayi.